2023
DOI: 10.1365/s43439-023-00089-8
|View full text |Cite
|
Sign up to set email alerts
|

An overview of cybercrime law in South Africa

Abstract: The COVID-19 pandemic has accelerated the uptake and use of information communication technologies and led to the digital transformation of different sectors of the economy. For South Africa, the COVID-19 pandemic struck at a time when the South African government had committed itself to leveraging technology for the benefit of its citizens, the private sector, and the public sector. By 2020, South Africa already had in place enabling policy and legal frameworks to assist with the regulation of activities taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The study carried by Pieterse (2021) indicated that the South African public sector is the major target of the cyberattackers. Mtuze and Musoni (2023) stated that the combat of cyberfraud under the Cybercrime Act passed in 2021 is more effective and sustainable compared to the era of the common law and ECTA; however, lack of skilled experts in the area of cybercrime investigation and evidence gathering remains a major challenge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study carried by Pieterse (2021) indicated that the South African public sector is the major target of the cyberattackers. Mtuze and Musoni (2023) stated that the combat of cyberfraud under the Cybercrime Act passed in 2021 is more effective and sustainable compared to the era of the common law and ECTA; however, lack of skilled experts in the area of cybercrime investigation and evidence gathering remains a major challenge.…”
Section: Literature Reviewmentioning
confidence: 99%